Imagined Communities? Relations of Social Identities and Social Organisation among Afghan Diaspora Groups in Germany and the UK. (2nd January 2017) - Fischer, Carolin
ABSTRACT: This paper engages with the complexity of diaspora by focusing on the links between self-identification, external categorisation and emerging ties among Afghans in Britain and Germany. Based on a qualitative case study and drawing on relational sociology, it demonstrates that family ties, class backgrounds, ethnicity and political affiliations inform peoples' attitudes towards each other and foster dynamics of inclusion, exclusion and group formation. Beyond particularistic identity categories there is evidence of an imagined community, which manifests itself in an implicitly shared concern about Afghanistan and a self-identification as 'being Afghan'. Yet this imagined community is rarely reflected in diasporic networks of Afghan co-nationals. A relational approach helps to explain how social identity categories come to be selectively enacted. The findings presented in this paper underline the importance of studying the making and unmaking of diaspora as part of wider social, political and historical processes.